Autocrine TGF-β1 drives tissue-specific differentiation and function of resident NK cells - Sparano, Colin; Solís-Sayago, Darío; Zangger, Nathan Sébastien; Rindlisbacher, Lukas; Van Hove, Hannah; Vermeer, Marijne; Westermann, Frederike; Mussak, Caroline; Rallo, Elisa; Dergun, Stanislav; Litscher, Gioana; Xu, Yishu; et al. (Journal of experimental medicine, 2024)
Group 1 innate lymphoid cells (ILCs) encompass NK cells and ILC1s, which have non-redundant roles in host protection against pathogens and cancer. Despite their circulating nature, NK cells can establish residency in selected tissues during ontogeny, forming a distinct functional subset. The mechanisms that initiate, maintain, and regulate the conversion of NK cells into tissue-resident NK (trNK) cells are currently not well understood. Here, we identify autocrine transforming growth factor-β (TGF-β) as a cell-autonomous driver for NK cell tissue residency across multiple glandular tissues during development. Cell-intrinsic production of TGF-β was continuously required for the maintenance of trNK cells and synergized with Hobit to enhance cytotoxic function. Whereas autocrine TGF-β was redundant in tumors, our study revealed that NK cell-derived TGF-β allowed the expansion of cytotoxic trNK cells during local infection with murine cytomegalovirus (MCMV) and contributed to viral control in the salivary gland. Collectively, our findings reveal tissue-specific regulation of trNK cell differentiation and function by autocrine TGF-β1, which is relevant for antiviral immunity.